Variations in leaf respiration and photosynthesis ratio in response to air temperature and water availability among Mediterranean evergreen species - Catoni, Rosangela; Gratani, Loretta (Journal of Arid Environments, 2014)
Net photosynthesis (PN) and leaf respiration (RL) of the evergreen species co-occurring in the Mediterranean maquis in response to water availability and air temperature variations were analyzed. The results underlined that the ratio RL/PN of the considered species ranged from 0.15 ± 0.08 (in winter) to 1.32 ± 0.80 (in summer). Variations of RL and PN during the year were attested by the PCA which was carried out using leaf physiological and morphological traits of the considered species. In particular, Cistus incanus having the highest mean yearly PN and RL rates and low leaf mass area (LMA) and leaf tissue density (LTD), was furthest from the other species emphasizing its drought semi-deciduous habitus, the highest photosynthetic capability in favorable conditions (spring), but low tolerance to drought. Erica multiflora and Rosmarinus officinalis were characterized by the highest LMA and LTD, low PN rates in drought and the lowest PN ones in spring. Erica arborea, Pistacia lentiscus, Phillyrea latifolia and Quercus ilex had the highest drought tolerance. Arbutus unedo and Smilax aspera were close to this group despite lower RL rates during the year. The xeromorphic leaves of the considered evergreen species (i.e. high LMA and LTD) favor carbon gain profits over transpiration losses during drought, nevertheless, the high construction cost of these leaf type justifies the relatively high RL rates.
Keywords: Leaf respiration; Mediterranean evergreen species; Net photosynthesis; Ratio RL/PN

Long-term monitoring of metal pollution by urban trees - Gratani, Loretta; Crescente, Maria Fiore; Varone, Laura (Atmospheric Environment, 2008)
The atmospheric pollution level in Rome was monitored in the year 2006. Five sites in the historical centre were considered. The concentration of Al, Fe, Cu, Zn, and Pb was analysed in washed and unwashed Quercus ilex leaf samples. Moreover, in order to verify the changes in atmospheric pollution in the historical centre of the city after the introduction of the limited trafﬁc zone (LTZ), previous data collected in the years 1979 and 1996 were also considered. The leaf’s internal concentration of Al, Fe, Cu, Zn, and Pb was 28, 22, 40, 77 and 37%, respectively, of the total concentration, and it was in the same range monitored in the years 1979 and 1996. The results underlined a signiﬁcant (p < 0.05) decreasing of metal concentration on unwashed leaves with on an average 92%, compared to ones monitored in the year 1979. The mean value of the total trafﬁc ﬂow during the limitated period (Monday to Friday, from 6:30 a.m. to 6:00 p.m, and Saturday from 2:00 to 6:00 p.m.) was 75.000 vehicles, compared to 90.000 ones before the electronic gates were activated; moreover, a 15% decrease in the daily trafﬁc peak (8:30–9:30 a.m) was monitored. The metal concentration in Q. ilex leaves was be related to motor vehicle emissions, conﬁrmed also by PCA. The data obtained on the leaf metal concentration trend in Rome, over a period of 27 years, underlined the importance of the City Council provisions. These results conﬁrmed the use of Q. ilex for long-term monitoring of metal concentration in those urban areas where the species was naturally present, and widely distributed in the landscape.
Keywords: Bio-monitor; Metal pollution; Quercus ilex; rome; Vehicular trafﬁc

Carbon sequestration by Quercus ilex L. and Quercus pubescens Willd. and their contribution to decreasing air temperature in Rome - Gratani, Loretta; Varone, Laura (Urban Ecosystems, 2006)
Carbon sequestration capability by Quercus ilex L and Quercus pubescens Willd., widely distributed in the city of Rome, and their contribution to decreasing air temperature were investigated. Crown volume is the most signiﬁcant (p < 0.01) variable explaining variation of air temperature below the tree crown. Q. pubescens gives a higher contribution to decreasing air temperature during the hottest months, due to its inherent larger crown volume than Q. ilex (252 ± 19 and 533 ± 52 m3 , respectively for the large size). Moreover, our results show the existence of a strong urban carbon dioxide dome with a peak CO2 concentration (on an average 432 ± 37 ppm) at polluted sites, 16% greater than at control sites. Total carbon sequestration is 84 ± 12 and 111 ± 9 Kg year−1 of CO2 for the small Q. ilex and Q. pubescens tree size,respectively, and 151 ± 10 and 185 ± 7 Kg year−1 of CO2 for the large Q. ilex and Q. pubescen tree size, respectively. Q. pubescens, by its higher total photosynthetic leaf surface area (39% higher than Q. ilex) and its higher mean yearly photosynthetic rates (48% higher than Q. ilex) seems to have a greater role than Q. ilex. However, taking into account the leaf longevity (i.e. 12 ± 3 months for Q. ilex and 4 ± 2 months for Q. pubescens), the evergreen species, by its continuous photosynthetic activity, contributes to reduce CO2 throughout the year, and in particular during the winter months, when trafﬁc volume has a pick, than Q. pubescens.
Keywords: Carbon Sequestration; evergreen and Deciduous species; heat island; lai; tree structure

Adaptive strategy at the leaf level of Arbutus unedo L. to cope with Mediterranean climate - Gratani, Loretta; Ghia, Emanuela (Flora-Morphology, Distribution, Functional Ecology of …, 2002)
The adaptive strategy of Arbutus unedo L. under Mediterranean climate seemed to be due to the high leaf area (LA = 11.1 ± 0.1 cm2 ) increasing the potential capacity of light interception, the high leaf lamina thickness (L = 395 ± 10 µm) increasing the potential capacity for gas exchange, and the steeper leaf inclination at midday (α up to 63.9 ± 0.3°) determining 48% of reduction of incident radiation on a sloping leaf surface (RI), which could be a prevention mechanism against the potential photoinhibition of water-stressed leaves during drought. Nevertheless, during the drought period the photosynthetic activity and the water use efficiency (WUE) of A. unedo were strongly reduced (≥ than 50% of the maximum). Principal component analysis (PCA) underlined the higher similarity of A. unedo and Quercus ilex L. from a physiological point of view (photosynthetic rates PN , transpiration rates E, stomatal conductance gs , sub-stomatal CO2 concentration Ci ) and for leaf inclination, and with Cistus incanus L. from a phenological (leaf-life span) and structural point of view (specific leaf area SLA and leaf tissue density LTD), for leaf temperature (Tl ) and for leaf water status (leaf water potential at midday Ψmin and relative water content RWC). Therefore A. unedo might be considered in the borderline between drought semi-deciduous species and evergreen sclerophyllous species.
Keywords: Gas exchange; leaf area; leaf inclination; leaf lamina thickness; leaf-life span; sclerophylly

Adaptive strategy at the leaf level of Arbutus unedo L. to cope with Mediterranean climate - Gratani, Loretta; Ghia, Emanuela (Flora-Morphology, Distribution, Functional Ecology of …, 2002)
The adaptive strategy of Arbutus unedo L. under Mediterranean climate seemed to be due to the high leaf area (LA = 11.1 ± 0.1 cm2 ) increasing the potential capacity of light interception, the high leaf lamina thickness (L = 395 ± 10 µm) increasing the potential capacity for gas exchange, and the steeper leaf inclination at midday (α up to 63.9 ± 0.3°) determining 48% of reduction of incident radiation on a sloping leaf surface (RI), which could be a prevention mechanism against the potential photoinhibition of water-stressed leaves during drought. Nevertheless, during the drought period the photosynthetic activity and the water use efficiency (WUE) of A. unedo were strongly reduced (≥ than 50% of the maximum). Principal component analysis (PCA) underlined the higher similarity of A. unedo and Quercus ilex L. from a physiological point of view (photosynthetic rates PN , transpiration rates E, stomatal conductance gs , sub-stomatal CO2 concentration Ci ) and for leaf inclination, and with Cistus incanus L. from a phenological (leaf-life span) and structural point of view (specific leaf area SLA and leaf tissue density LTD), for leaf temperature (Tl ) and for leaf water status (leaf water potential at midday Ψmin and relative water content RWC). Therefore A. unedo might be considered in the borderline between drought semi-deciduous species and evergreen sclerophyllous species.
Keywords: Gas exchange; leaf area; leaf inclination; leaf lamina thickness; leaf-life span; sclerophylly

Shoot growth efficiency and production of Quercus ilex L. in different climates - Crescente, M F; Gratani, Loretta; Larcher, Walter (Flora-Morphology, Distribution, …, 2002)
Structural and functional traits of Quercus ilex L. were monitored in plants growing in the climax area (Castelporziano, Rome; site A) and at the northern distribution limit (Nago, Trento; site B) in Italy. The most distinctive climatic differences between the two sites were duration and frequency of drought, heat spells in summer at site A, and the occurrence of frost and sub-zero temperatures in winter at site B. The potential productivity of Quercus ilex lies in its tendency to be slow growing with maximum vegetative activity from the end of April to the end of June at Castelporziano, and from the middle of May to the middle of July at Nago, when air temperatures favoured the highest photosynthetic rates (90–100%). The lower shoot biomass production at site B was due to the lower relative growth rates in shoot length (RGRl < 20%) and in shoot dry mass (RGRm <11%). The lower shoot length growth efficiency (LE < 62%) at the northern limit was related to the low temperatures in winter and beginning of spring which reduced favourable periods (<20% than site A) for photosynthetic carbon gain and growth dynamics. It resulted in a lower total leaf surface area per shoot (<60% than site A) and a reduced shoot leaf mass (<31%).
Keywords: Net photosynthesis; Phenology; Quercus ilex L; Relative growth rate; shoot length growth efficiency; shoot production

Shoot growth efficiency and production of Quercus ilex L. in different climates - Crescente, M. F.; Gratani, Loretta; Larcher, Walter (Flora-Morphology, Distribution, …, 2002)
Structural and functional traits of Quercus ilex L. were monitored in plants growing in the climax area (Castelporziano, Rome; site A) and at the northern distribution limit (Nago, Trento; site B) in Italy. The most distinctive climatic differences between the two sites were duration and frequency of drought, heat spells in summer at site A, and the occurrence of frost and sub-zero temperatures in winter at site B. The potential productivity of Quercus ilex lies in its tendency to be slow growing with maximum vegetative activity from the end of April to the end of June at Castelporziano, and from the middle of May to the middle of July at Nago, when air temperatures favoured the highest photosynthetic rates (90–100%). The lower shoot biomass production at site B was due to the lower relative growth rates in shoot length (RGRl < 20%) and in shoot dry mass (RGRm <11%). The lower shoot length growth efficiency (LE < 62%) at the northern limit was related to the low temperatures in winter and beginning of spring which reduced favourable periods (<20% than site A) for photosynthetic carbon gain and growth dynamics. It resulted in a lower total leaf surface area per shoot (<60% than site A) and a reduced shoot leaf mass (<31%).
Keywords: Net photosynthesis; Phenology; Quercus ilex L; Relative growth rate; shoot length growth efficiency; shoot production

Leaf temperature effects on gas exchange in Quercus ilex L. growing under field conditions - Gratani, Loretta (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2000)
ABSTRACT Gas exchange temperature dependence in Quercus ilex shrubs growing in the Mediterranean maquis was analysed. The gas exchange trend was monitored during the year: photosynthetic activity (A net) reached the highest average rates in early spring and autumn (12.5 µmol m-2s-1 was the absolute maximum A net measured) and the lowest rates were monitored in the middle of June. There was a good correlation (r = 0.72) between A net and g s (A net = 4.1246 ln g s + 4316; P < 0.01), indicating that stomatal control of CO2 diffusion plays an important role in controlling photosynthetic activity. Leaf temperature allowing the highest photosynthetic and stomatal conductance rates of Quercus ilex were in the range 17.5 ? 29°C. A net and gs dropped below half its maximum value when leaf temperatures were below 11.5°C and above 35.7°C. Transpiration rates (E) were strongly related to leaf temperature; E increased as leaf temperature increased and the highest E rates were monitored in June, despite a 46% decrease in g s. Leaf water loss from transpiration, during the drought period, could result in leaf water stress which would exacerbate heat effects on photosynthesis. During summer, the increase in leaf temperatures decreased g s which in turn decreased A net. Consequently, stomatal control in Quercus ilex may be considered as an adaptive strategy during drought.
doi: 10.1080/11263500012331350295
Keywords: Leaf temperature; photosynthetic activity; Quercus ilex; Stomatal conductance

Characterization of mineral content in Quercus ilex leaves by photon and neutron activation analysis - Bruno, Franco; Capannesi, Geraldo; Gratani, Loretta; Manes, Fausto (Giornale botanico italiano, 1980)
Abstract As part of a research on the holm oak stand and the Mediterranean « macchia » of Castelporziano, this study has provided the mineral characterization of Quercus ilex leaves by means of photon and neutron activation analysis. Although there is no evidence to indicate a selective distribution of the elements in the trees' crowns, some correlations are of considerable interest. Highly significant correlation coefficients are observed for the following pairs of elements: Fe-Sc, Fe-Cr, Fe-Th, Fe-Eu.
doi: 10.1080/11263508009427960
Keywords: Castelporziano (voyant); leaves and twigs; nuclear analysis; Quercus ilex; Trace Elements